Thermoelectric properties of layered NaSbSe2. (8th May 2018) - Putatunda, Aditya; Xing, Guangzong; Sun, Jifeng; Li, Yuwei; Singh, David J
Abstract: We investigate ordered monoclinic NaSbSe2 as a thermoelectric using first principles calculations. We find that from an electronic point of view, ordered and oriented n -type NaSbSe2 is comparable to the best known thermoelectric materials. This phase has a sufficiently large band gap for thermoelectric and solar absorber applications in contrast to the disordered phase which has a much narrower gap. The electronic structure shows anisotropic, non-parabolic bands. The results show a high Seebeck coefficient in addition to direction dependent high conductivity. The electronic structure quantified by an electron fitness function is very favorable, especially in the n -type case.